Basic counseling responses in groups - Haney, Hutch; Leibsohn, Jacqueline; Brooks/Cole Thomson Learning (Belmont, CA : Brooks/Cole Thomson Learning, 2001)
This video contains real counseling sessions with unscripted, unrehearsed individuals. also watch and learn how experienced group leaders guide their groups beyond initial'conflict' and'chaos' to problem solving and cohesion
Title from cover
System requirements for accompanying CD-ROM: Microsoft Windows95 or Windows98; 120-mhz Pentium
Keywords: Group counseling; Group psychotherapy; Group counseling -- Problems, exercises, etc; Group psychotherapy -- Problems, exercises, etc